Soccer School Coaching System as a Nursery Base Soccer Club Players in PERSIK Kendal - Pramanto, Widya; Pramono, Harry; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
Problem with this research is that there has not been a maximum level of coaching at the Soccer School in Kendal Regency. This study aims to analyze: Curriculum and training programs, Coaches, Athletes, Facilities and infrastructure, Management, Coaching system at the Soccer School in Kendal Regency. This research is qualitative research with data triangulation on data analysis techniques.The results of the study show that: Not all SSBs in Kendal Regency make curriculum and training programs, Not all SSB trainers in Kendal Regency have football license levels, Athletes/students of SSB in Kendal Regency have been classified according to age, facilities and infrastructure at SSB in Kendal District have fulfilling to carry out the coaching program, There is a management or organizational structure with a clear division of tasks at SSB in Kendal District, the Coaching System at the Football School in Kendal Regency has not been going well. The conclusion of this research is: The preparation of curriculum and training programs on SSB in Kendal Regency has not been implemented well. The trainers at SSB in Kendal Regency have not yet qualified as good trainers. Athletes, infrastructure, and management at SSB in Kendal Regency are good enough. The guidance system at SSB in Kendal Regency has not run well.